In‐home use of a hybrid closed loop achieves time‐in‐range targets in preschoolers and school children: Results from a randomized, controlled, crossover trial. Issue 7 (20th April 2022) - von dem Berge, Thekla; Remus, Kerstin; Biester, Sarah; Reschke, Felix; Klusmeier, Britta; Adolph, Kerstin; Holtdirk, Anette; Thomas, Andreas; Kordonouri, Olga; Danne, Thomas; Biester, Torben
Abstract: Aim: To obtain additional information on the incremental differences between using a sensor‐augmented pump (SAP) without automated insulin delivery (AID), using it with predictive low‐glucose management (PLGM) or as hybrid closed loop (HCL), in preschool and school children. Methods: We conducted a monocentric, randomized, controlled, two‐phase crossover study in 38 children aged 2‐6 and 7‐14 years. The primary endpoint was the percentage of time in range (TIR) of 70‐180 mg/dl. Other continuous glucose sensor metrics, HbA1c, patient‐related outcomes (DISABKIDS questionnaire, Fear of Hypoglycaemia Survey) and safety events were also assessed. Results from 2 weeks of SAP, 8 weeks of PLGM and 8 weeks of HCL were compared using a paired t‐test or Wilcoxon signed‐rank test. Results: Overall, we found a high rate of TIR target (>70%) achievement with HCL in preschool (88%) and school children (50%), with average times in Auto Mode of 93% and 87%, respectively. Preschool children achieved a mean TIR of 73% ± 6% (+8% vs. SAP, +6% vs. PLGM) and school children 69% ± 8% (+15% vs. SAP and + 14% vs. PLGM). Overall, HbA1c improved from 7.4% ± 0.9% to 6.9% ± 0.5% ( P  = .0002). Diabetes burden and worries and fear of hypoglycaemia remained at low levels, without significant changes versus PLGM. No events of severe hypoglycaemia or diabetic ketoacidosis occurred. Conclusions: Preschool children profit from AID at least as much as those aged 7 years and older. To ensure safe use and prescribing modalities, regulatory approval is also required for young children.